Analisis Dampak Kepemimpinan, Disiplin Kerja, Kompetensi Terhadap Kinerja: Studi Empiris Pada SMPN 1 Bangkinang Kota - Yusmawati Yusmawati; Suarni Norawati; Zamhir Basem (eCo-Buss, 2022)
This study aims to analyse the effect of leadership, discipline work, and teacher competence on teacher performance. Several factors examined teacher performance. These are leadership, discipline work and teacher competence. Data were collected using questionnaires, observations, and interviews. The sample study was 76 teachers at SMPN 1 Bangkinang Kota. The data analysis technique was carried out with the stages of descriptive analysis and hypothesis testing. The results reveal that simulant result leadership, discipline work and teacher competence have a positive and significant effect on the teacher’s performance at SMPN 1 Bangkinang City, while the leadership partially has no significant effect on teacher performance. Discipline and competence have been shown to have a significant effect on teacher performance